2000
DOI: 10.1080/026782900202813
|View full text |Cite
|
Sign up to set email alerts
|

Electrically controlled director slippage over a photosensitive aligning surface; in-plane sliding mode

Abstract: We have studied the electro-optical characteristics of a homogeneously aligned nematic liquid crystal (LC) with weak planar anchoring of the director at the bounding substrates. By using the in-plane switching (IPS) of the LC which is achieved by an in-plane electric eld, the driving voltage was con rmed to be far less than that of the conventional IPS mode in which both substrates possess strong anchoring characteristics. Moreover, because of the absence of strong subsurface director deformations, the cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In consideration of different anchoring forces, the response times of three cases are not only dependent on d, γ and K 22 , but also related to the surface anchoring energy (W). Therefore, the modified rising and decaying times have been shown in the following forms [12][13][14]:…”
Section: Liquid Crystals 1059mentioning
confidence: 99%
See 2 more Smart Citations
“…In consideration of different anchoring forces, the response times of three cases are not only dependent on d, γ and K 22 , but also related to the surface anchoring energy (W). Therefore, the modified rising and decaying times have been shown in the following forms [12][13][14]:…”
Section: Liquid Crystals 1059mentioning
confidence: 99%
“…For IPS LC cell in consideration of cell surface boundary condition, the implicit dependence of threshold voltage (V th ) and anchoring energy (W) is given by [13] …”
Section: Liquid Crystals 1059mentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the azimuthal anchoring energy of photoaligning materials is rather small (about 1-7 × 10 -6 J/m 2 ), which is about an order of magnitude smaller than the value obtained by the rubbing method. [11][12][13][14] The azimuthal anchoring energy W ϕ of a photoaligned substrate was measured. 15 It was found that the anchoring energy was very high and >10 -4 J/m 2 , which is the same as the anchoring energy of the rubbed polyimide (PI) layer.…”
Section: Characteristics Of Azo-dye Photoalignmentmentioning
confidence: 99%
“…For example, a weak LC alignment is known to reduce the operating voltage and increase the response time [27], [28]. In the past decades, several LC alignment techniques were developed to induce uniform liquid crystal orientations [29].…”
Section: Introductionmentioning
confidence: 99%